Integration of Clustering System and Joint Venture Business Model for CCUS Deployment: A Case Study in South Sumatra Region - Prajna Indrasuta, Martinus Bhima; Hutagalung, Adryan Samuel; Putra, Saeful Ghofar Zamianie; Saga, Radista; Rizky, Aurellia Anindita (Indonesian Journal of Energy, 2023)
Carbon Capture, Utilization, and Storage (CCUS) have been a 'buzzword' for the past two years, especially in Indonesia, a developing country committed to achieving net-zero emissions. However, 43% of global CCUS projects were still terminated or put on hold, mainly driven by economic inability and public acceptance. Therefore, a suitable business model and clustering system must be proposed to make carbon sequestration projects economically attractive in Indonesia. Under the Analytical Hierarchy Process (AHP) assessment collaborating with the previous study conducted by Center of Excellence ITB and Lemigas, clustering systems can be deployed in three regions: South Sumatra, West Java, and East Kalimantan. The selected CO2 sources consist of various industrial sectors surrounding the fields, aiming to facilitate the source's matching process to the possible sink. Thus, it is obtained that the Talang Jimar field (South Sumatra) becomes the highest priority and the most probable sink point with 0.584 GtCO2 storage and an annual sink capacity of 0.0292 GtCO2 for 20 years storage period. Integrating CCUS deployment in Talang Jimar with a clustering system and advanced capturing technology seriously adds commercial value to the project. A carbonate fuel cell is the proposed capturing technology for coal power plants, with expected CO2 capture efficiency by 90% and reduced electricity cost by 33%. These developing technologies and clustering systems are forcing companies to find more efficient business models to compete in the carbon market. In this study, a joint venture scheme is applied to specify the CO2 value chain in this project and to cover the capturing and transportation cost through the joint-stock cooperative system, under sharing percentage assumptions of 40% for the capturing company, 30% for storage, and 30% for transport.